“You Can if You Must, but We’d Prefer It if You Didn’t”: Can We Develop a More Pastoral Theology of Abortion? - Percy, Emma (Anglican theological review, 2024)
Some Anglican Churches have adopted permissive acceptance of abortion while expressing the hope it will be rare. This presumes competition between the welfare of the woman and that of her unborn child. In this article, I will critique statements from the Church of England and The Episcopal Church, United States through a feminist-pastoral perspective. I will look principally at early abortions which are often a response to unintended pregnancy. I will discuss abortion alongside miscarriage challenging pro-natal assumptions inherent in the Christian tradition. I will also discuss the costs of pregnancy. In doing so, I will draw on the pragmatic and pastoral strengths of Anglican theology to argue for a position that respects and supports women’s moral decision to not bring a new life into being, recognizing this can be a considered response for the welfare of a potential child as well as for the woman.